2015
DOI: 10.3998/ark.5550190.p009.353
|View full text |Cite
|
Sign up to set email alerts
|

5-(3-Phosphonated 1H-1,2,3-triazol-4-yl)isoxazolidines: synthesis, DFT studies and biological properties

Abstract: 5-Triazolyl-2-methylisoxazolidin-3-yl 3-phosphonates have been synthesized by 1,3-dipolar cycloaddition of N-methyl-C-diethoxyphosphorylnitrone and vinyl triazoles. The process showed a complete regioselectivity and a nearly exclusive cis stereoselectivity. M062X/6-31G(d,p) calculations rationalize the regio-and the stereochemical results. The formation of a hydrogen bond along a particular reaction channel significantly stabilizes both transition states and products related to cis-adducts. Biological tests in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The phosphonated derivatives had to be activated by intracellular phosphorylases and are also more resistant to enzymatic degradation because of the insensitive P−C bond. Their synthesis and biological evaluations were reviewed by Giofre et al 265 Homonucleosides, having a methyl group between the ring and the nucleobase, were also designed with the same goal. C-Nucleosides are physiologically present (i.e., pseudo uridine, for example).…”
Section: Natural Building Block Mimeticsmentioning
confidence: 99%
“…The phosphonated derivatives had to be activated by intracellular phosphorylases and are also more resistant to enzymatic degradation because of the insensitive P−C bond. Their synthesis and biological evaluations were reviewed by Giofre et al 265 Homonucleosides, having a methyl group between the ring and the nucleobase, were also designed with the same goal. C-Nucleosides are physiologically present (i.e., pseudo uridine, for example).…”
Section: Natural Building Block Mimeticsmentioning
confidence: 99%
“…Higher SI values with respect to AZT indicated that the compounds were endowed with low cytotoxicity. 28 All these research activities were furtherly developed 29 and summarized by the Catania and Messina research groups in a Mini-Review dealing with phosphonated N,O-nuclesides 30 and in a review on the use of isoxazolidines as scaffolds for the preparation of biologically active compounds. 31 A general overview of the use of phosphonated nitrones for the synthesis of nucleoside analogues is given by Kokosza, Balzarini, and Piotrowska in a paper published on Nucleosides, Nucleotides and Nucleic Acids in 2014.…”
Section: Scheme 5 Synthesis Of Phosphonated No-nucleosides 15mentioning
confidence: 99%